Pengajian Remaja Dan Pembentukan Moral: Studi Kasus Di Jawa Barat Berbasis Komunitas - Lia Siti Nur Rani; Nia Oktaviani (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyse the role of youth religious study groups in shaping the moral character of the younger generation at the At-Taqwa Mosque in Kampung Sayang, Sumedang Regency. The study employs a qualitative approach using a case study design to gain an in-depth understanding of the phenomenon from the informants’ perspectives. Data collection techniques included interviews, observation and documentation. The findings are expected to demonstrate that youth religious study groups play a strategic role in the internalisation of moral values through habit formation, role modelling, and religious social interaction. Furthermore, the success of moral development is influenced by supporting factors such as the religious environment and the role of mentors, as well as inhibiting factors such as the influence of digital culture and low youth participation. This study concludes that youth religious study groups are an effective means of shaping the character of the younger generation if managed in a structured and contextually appropriate manner.